Associations between AR-V7 status in circulating tumour cells, circulating tumour cell count and survival in men with metastatic castration-resistant prostate cancer. (November 2019) - Belderbos, Bodine P.S.; Sieuwerts, Anieta M.; Hoop, Esther Oomen-de; Mostert, Bianca; Kraan, Jaco; Hamberg, Paul; Van, Mai N.; Beaufort, Corine M.; Onstenk, Wendy; van Soest, Robert J.; Martens, John; Sleijfer, Stefan; et al.
Abstract: Background: The interpretation of the presence of AR-V7 in circulating tumour cells (CTCs) in men with metastatic castration-resistant prostate cancer (mCRPC) remains to be elucidated. AR-V7 may hold promise as a predictive biomarker, but there may be prognostic impact of AR-V7 positivity as well. To investigate the clinical value of AR-V7, we determined whether AR-V7 detection in CTCs in patients with mCRPC is associated with CTC counts and survival. Methods: Between December 2011 and January 2019, three prospective clinical trials collected clinical data of patients with mCRPC, who progressed after docetaxel and/or enzalutamide or abiraterone. Baseline (and follow-up) blood samples were withdrawn determining CTC count and AR-V7 expression. The majority of patients started cabazitaxel as the next line of treatment after AR-V7 characterisation. Results: A total of 127 samples were evaluable for the analysis of CTC count versus AR-V7 status. Although an association was observed between AR-V7 and CTC count in all patients with mCRPC (p = 0.017), no such association was found in the prognostic unfavourable subgroup of patients with ≥5 CTCs. After adjusting for clinical prognostic factors, AR-V7 expression in CTCs was not associated with overall survival (hazard ratio = 1.33, 95% confidence interval = 0.81–2.15, p = 0.25). Conclusion: We found that AR-V7 expression in CTCs had no additional prognostic value in patients with mCRPC, mostly treated with cabazitaxel. In patients with mCRPC with a predefined worse prognosis of a higher CTC count (≥5), a predictive biomarker is an important unmet medical need. Prospective trials should investigate whether AR-V7 detection in CTCs may guide treatment selection for these adverse prognosis patients. Highlights: AR-V7 in circulating tumor cells had no additional prognostic value in mCRPC patients. A predictive biomarker is an important unmet need in prostate cancer treatment. Prospective trials should investigate if AR-V7 detection may guide treatment selection.